Prototype Sistem Kendali Sliding Gate Berbasis Arduino dan Radio Frequency Identification (RFID) di Politeknik Penerbangan Jayapura - M. Akbar Kadir Djaelani; Avelira Perangin-angin; Daniel Lorenzo Sahara; Pipa Biringkanae; Gabriel Gema Lokananta (SKY EAST: Education of Aviation Science and Technology, 2024)
Jayapura Aviation Polytechnic is an educational institution managed as a Public Service Agency (BLU) under the Ministry of Transportation, which functions not only as an education provider but also as a source of income. Effective and efficient management is the key to supporting public services and increasing the sense of comfort for all users of the facility, including students, employees, and visitors. This study aims to create a prototype of a sliding gate control system based on Arduino and radio frequency identification (RFID) to improve efficient security facilities in the Jayapura Aviation Polytechnic environment. The research method used is Research and Development (R&D) level 4, with research stages including literature studies, field observations, and interviews and discussions with electrical engineering experts and security officers. The test results show that this sliding gate control system is able to automate the opening and closing of the gate by utilizing RFID tags for entry and exit access, as well as full control by the administrator. The use of Arduino as a microcontroller platform simplifies the development and programming process. In addition, the RFID components used are easy to obtain and relatively inexpensive, this system can also be used as a learning tool for researchers and cadets. Thus, the prototype of the sliding gate control system based on Arduino and radio frequency identification (RFID) shows good performance and has the potential to increase operational efficiency at the Jayapura Aviation Polytechnic.